Role of microbial electrosynthesis system in CO2 capture and conversion: a recent advancement toward cathode development - Ibrahim, Irwan; Salehmin, Mohd Nur Ikhmal; Balachandran, Krishan; Hil Me, Muhammad Farhan; Loh, Kee Shyuan; Abu Bakar, Mimi Hani; Jong, Bor Chyan; Lim, Swee Su (Frontiers in Microbiology, 2023)
Microbial electrosynthesis (MES) is an emerging electrochemical technology currently being researched as a CO2 sequestration method to address climate change. MES can convert CO2 from pollution or waste materials into various carbon compounds with low energy requirements using electrogenic microbes as biocatalysts. However, the critical component in this technology, the cathode, still needs to perform more effectively than other conventional CO2 reduction methods because of poor selectivity, complex metabolism pathways of microbes, and high material cost. These characteristics lead to the weak interactions of microbes and cathode electrocatalytic activities. These approaches range from cathode modification using conventional engineering approaches to new fabrication methods. Aside from cathode development, the operating procedure also plays a critical function and strategy to optimize electrosynthesis production in reducing operating costs, such as hybridization and integration of MES. If this technology could be realized, it would offer a new way to utilize excess CO2 from industries and generate profitable commodities in the future to replace fossil fuel-derived products. In recent years, several potential approaches have been tested and studied to boost the capabilities of CO2-reducing bio-cathodes regarding surface morphology, current density, and biocompatibility, which would be further elaborated. This compilation aims to showcase that the achievements of MES have significantly improved and the future direction this is going with some recommendations.